Association of Carbapenemase-Producing Enterobacterales Detected in Stream and Clinical Samples - Sung, Gyung-Hye; Kim, Si Hyun; Park, Eun Hee; Hwang, Suk Nam; Kim, Jea-Dong; Kim, Gyu Ri; Kim, Eun-Young; Jeong, Joseph; Kim, Sunjoo; Shin, Jeong Hwan (Frontiers in Microbiology, 2022)
carbapenem, carbapenemase-producing Enterobacterales, antimicrobial resistance, Stream, Multi-locus sequence typing